RFM Segmentation Analysis for Determine Online Marketing Strategy: the Soul Coffee Mate Case Study - Aldyah, Tika; Sugino, Agus; Muzakkar, Milastri; Heikal, Jerry (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the impact of digital marketing on a cafe named The Soul, located in Jakarta. The cafe experienced a recent decline in sales attributed to factors such as new competitors, closures of nearby establishments, diminishing trends in working from cafes, and changes in customer demographics. Recognizing the need for a robust online marketing strategy, researchers aim to analyze customer segmentation using the RFM model, focusing on Recency, Frequency, and Monetary aspects of transactions over the past 11 months. The goal is to understand customer behavior, design effective online marketing strategies, and ultimately boost the company's revenue. The RFM analysis results identified eight customer segments for The Soul: Soulmate, Loyal Customers, Potential Loyalists, Promising, New User, At Risk, Can't Lose Them, and Hibernating. Proposed strategies include personalized promotions for different customer segments, such as monthly appreciation for